2015
DOI: 10.1080/00207543.2015.1082042
|View full text |Cite
|
Sign up to set email alerts
|

A bi-objective location-inventory model with capacitated transportation and lateral transshipments

Abstract: We integrate location and inventory decisions in a three-echelon distribution network model with multiple products, capacitated in-house fleet and proactive transshipments between depots. The problem was originally motivated by the real-life case of a leading company in consumers' household goods. The company offers a wide range of products which are different from demand pattern and shortage viewpoints. One of the product groups has seasonal trend with possibly lost sales during high seasons and backlog in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…There is promising room for contributing to the literature of M-O LIP models, as only a few studies of this type can be found. Surprisingly, all of the existing M-O cases are by some means related to the optimization of customer service level [89][90][91][92]. This type also includes further relevant measures, such as the cost of lost sales by Aryanezhad et al [93] and delay by Javid et al [94,95].…”
Section: Location Inventory Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is promising room for contributing to the literature of M-O LIP models, as only a few studies of this type can be found. Surprisingly, all of the existing M-O cases are by some means related to the optimization of customer service level [89][90][91][92]. This type also includes further relevant measures, such as the cost of lost sales by Aryanezhad et al [93] and delay by Javid et al [94,95].…”
Section: Location Inventory Problemsmentioning
confidence: 99%
“…In terms of stochasticity, Sadjadi et al [98] employ queuing theory to deal with uncertainty. Fuzzy approaches are also applied by several LIP papers for the same purpose [50,89,99]. Some other articles [23,29,65,91,93,94,100,101] used the advantage of the probability distributions to address stochasticity, and the remaining models are deterministic.…”
Section: Location Inventory Problemsmentioning
confidence: 99%
“…Although less studied, MO-ILMs have also been proposed in the literature (see [1,3]). In [1] the authors design a distribution network model considering three-echelon and integrating location and inventory decisions.…”
Section: Inventory-location Modellingmentioning
confidence: 99%
“…In [1] the authors design a distribution network model considering three-echelon and integrating location and inventory decisions. The objectives considered in their model are the overall profit and the level of service as a measure of the customers' dissatisfaction.…”
Section: Inventory-location Modellingmentioning
confidence: 99%
See 1 more Smart Citation